USER EXPERIENCE (UX) OF MULTIMEDIA; PROGRAM OF AUTO PLAY MEDIA STUDIO FOR TEACHER PROFESSIONAL EDUCATION (PPG) - Mohammad Salehudin; Etty Nurbayani; Rostanti Toba (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
A factor that can influence the success of learning process is the use of learning media. Therefore, this research aims to evaluate the user experience of multimedia using the program of Auto play media studio for Teacher Professional Education (PPG). The research problem is how the teachers use multimedia in learning and how the teachers develop the multimedia by themselves using the computer technology program of media studio auto play. The research method is the user experience (UX) using the instrument from User Experience Questionnaire (UEQ) of Indonesian version, because there are several language versions of the questionnaire built and validated (for example, English, Spanish, Portuguese, etc.) These versions are available for free and online at www.ueq-online.org. The research result from the test of UEQ is that there are five scales which are categorized as excellent; they are Attractiveness, Efficiency, Dependability, Stimulation and Novelty, whereas the scale of Perspicuity is categorized of Above Average according to the interval benchmark of UEQ. All scores are above 0,08 shows that the evaluation of UX is positive. It can be concluded that the multimedia learning using the program of is very good – satisfying to use for the Teacher Professional Education for Islamic Education subject (PAI).